1997
DOI: 10.1159/000190295
|View full text |Cite
|
Sign up to set email alerts
|

Carvedilol Protects against Glomerulosclerosis in Rat Remnant Kidney without General Changes in Antioxidant Enzyme Status

Abstract: Nephron loss leads to increased production of reactive oxygen intermediates. We measured the effect of carvedilol, a β-blocking drug with radical scavenging properties, on renal function, glomerulosclerosis, antioxidant enzyme status and in vivo hydrogen peroxide (H2O2) production in rats with chronic renal failure caused by 5/6 nephrectomy (remnant kidney) and compared results to data obtained with propranolol, a β-blocking drug without scavenging characteristics. Carvedilol and proprano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 17 publications
1
14
0
1
Order By: Relevance
“…There may also be substantial differences between different ␤-blocking drugs. Third-generation ␤-blockers, such as carvedilol and nebivolol, seem to have more protective effects than traditional ␤-blockers, 47,63 possibly via stimulation of NO release. 58 In fact, carvedilol is even protective in acute renal failure after gentamicin.…”
Section: ␤-Adrenergic Receptor Blockadementioning
confidence: 99%
See 1 more Smart Citation
“…There may also be substantial differences between different ␤-blocking drugs. Third-generation ␤-blockers, such as carvedilol and nebivolol, seem to have more protective effects than traditional ␤-blockers, 47,63 possibly via stimulation of NO release. 58 In fact, carvedilol is even protective in acute renal failure after gentamicin.…”
Section: ␤-Adrenergic Receptor Blockadementioning
confidence: 99%
“…40,[62][63][64][65] Renal protection by ␤-blockade has also been observed in NOS inhibition 66 -68 and in stroke-prone SHR on high-salt intake. 47 Experimental studies of renal injury that evaluated adrenergic blockade are listed in Table 1.…”
Section: ␤-Adrenergic Receptor Blockadementioning
confidence: 99%
“…When studied, the efficacy was comparable to that of interference with the RAS (52, 82, 90) or with a calcium antagonist (94). Both ␣-adrenergic blockade (51, 85,87,88,90,91) and ␤-adrenergic blockade (51, 80,83,84,92,93) have protective action, and summation of their effects occurs (51). In a model of type 2 diabetes, combining adrenergic blockade with RAS blockade offered only slightly better protection (90), which may not be surprising because there is probably much overlap in downstream pathways leading to renal damage.…”
Section: Sympathetic Hyperactivity and Kidney Damagementioning
confidence: 99%
“…Nonetheless, attenuation of progression of renal failure by inhibition of sympathetic action, by either renal denervation or pharmacologic agents, has been found in diverse rat models of CRF, such as subtotal nephrectomy by surgical excision (52, 80), or by infarction (81)(82)(83)(84), NOS inhibition (85-88), streptozotocininduced diabetes (89), and type 2 diabetes in corpulent SHR (90,91) and in salt-loaded stroke-prone SHR (92,93). When studied, the efficacy was comparable to that of interference with the RAS (52, 82, 90) or with a calcium antagonist (94).…”
Section: Sympathetic Hyperactivity and Kidney Damagementioning
confidence: 99%
“…Experimental studies showed that carvedilol can reduce focal sclerosis, lipid peroxidation, and serum urea and creatinine levels. [21] Various hypotheses could be advanced to explain this effect of carvedilol. Unlike conventional beta blockers, carvedilol does not reduce glomerular filtration rate, effective renal plasma flow, blood urea nitrogen, or serum creatinine, and significantly decreases renal vascular resistance.…”
Section: Discussionmentioning
confidence: 99%